Tax and noncommunicable diseases attributable to tobacco and alcohol consumption in 5 Sub-Saharan African countries - Moyo, Machiru; Chirwa, Gowokani Chijere; Nyirenda, Thomas; Matanje, Beatrice Lydia (Frontiers in Public Health, 2025)
BackgroundIncreased taxation on alcohol and tobacco is among the cost-effective measures used to deal with the burden of noncommunicable diseases (NCDs) globally. Despite adopting such efforts, the impacts of taxation on alcohol and tobacco are yet to be fully understood.ObjectiveThe study's objective is to find empirical evidence regarding changes in the NCD mortality rate associated with changes in the tax rates of tobacco and alcohol.MethodsThe study adopted the System Generalized Method of Moments (SGMM) to explore the relationship between levels of taxes and NCD mortality rates. The SGMM allowed the inclusion of the dependent variable as an explanatory variable, assuming reverse causality was assumed.ResultsThere appears to be a negative relationship between increased taxes and the rates of NCDs. Specifically, we provide empirical evidence supporting the negative association between taxes on alcohol and tobacco cigarettes and the mortality rates from NCDs, which aligns with the propositions advocated by the World Health Organization (WHO). Additionally, the interaction between alcohol taxes on spirits and beer indicates a possibility of complementarity, consistent with taxation principles. Notably, we also observed that higher tobacco cigarette prices are negatively associated with NCD mortality rates.ConclusionThe results indicate that increasing taxes on major health risk factors is necessary to reduce non-communicable diseases (NCDs). Implementing these tax increases will likely help achieve Sustainable Development Goal 3.4, which aims to reduce NCD mortality by one-third by the year 2030.